Effect of Consumer Awareness of Education Material, Source of Information, and Value of Materialism on Behavior as A Smart Adolescent Consumer - Mia Fitriyah Setianingrum; Lilik Noor Yuliati (Journal of Consumer Sciences, 2017)
This study aims to analyze the effect of consumer awareness about education material, source of information, and value of materialism toward behavior as smart consumer on junior high school student in urban and rural areas of Bogor. Samples in this study are 9th grade junior high school students as much as 125 students that consisting of 62 students in urban and 63 students in rural areas. The sampling technique is cluster random sampling with the consideration that students have obtained consumer education materials on social sciences and Indonesian language for grade 7 to grade 9. Data were collected by self-administered technique using questionnaires. The results showed that there are differences in consumer awareness about education material, source of information, and objective knowledge of students in urban and rural areas. Gender and source of information affect the behavior as smart consumer on junior high school students.